Spatial heterogeneity of soil phosphorus influencing bacterial functional adaptations in alkaline calcareous soils - Tabbasum, Saira; Yahya, Mahreen; Zia, Munir; Haq, Midrar ul; Anwar, Samina; Khan, Usama Azeem; Mahreen, Naima; Ejaz, Khansa; Tarkka, Mika Tapio; Yasmin, Sumera (Frontiers in Microbiology, 2026)
To enhance sustainable soil fertility and efficient phosphorus (P) management, phosphate-solubilizing bacteria (PSB) play a central role in solubilizing soil mineral phosphorus by releasing organic acids and acidifying micro-niches. Thus far, the influence of spatial P heterogeneity on bacterial eco-physiological adaptations to P-limited, alkaline soils remains poorly understood. This study examined how soil edaphic factors vary across major wheat-growing regions, assessing their influence on the abundance and functional properties of culturable PSB. Soil available P was the strongest predictor of culturable bacterial abundance, with a threshold of P < 6.3 mg kg–1 dry soil driving major variations. At low P levels, organic matter played a key role, while at higher P levels, potassium (K ≥ 123) and pH further shaped bacterial abundance. Low-P soil PSB (LPSB) secreted elevated levels of organic acids such as malic, succinic, gibberellic and citric acid, but low levels of indole acetic acid. A clear trade-off was observed between P solubilization and growth-related traits: LPSB invested more in acquiring resources (e.g., producing siderophores and organic acids) and less in synthesizing phytohormones. A net house study showed that LPSB contribute to plant growth. Plants with 70% phosphate fertilization (P70) and PSB inoculation reached the yield levels comparable to those with 100% fertilization without the PSB, indicating the potential of PSB to reduce dependency on fertilizers. This was associated with a significant increase in wheat biomass (24.3%), yield (28.53%) and P use efficiency (31.66%) by LPSB inoculation compared to the control P70. Our findings emphasize the importance of microbial functional plasticity in enhancing P use efficiency in P-limited soil, offering a basis for developing climate-smart bioformulations to improve sustainable crop productivity.